Design and Evaluation of an Affordable Drip Irrigation System for Backyard Garden in the Forest-Savannah Transition Zone of Ghana - Kotei, Richard; Atakora, Eric Takyi; Asiedu, Emmanuel Kwesi; Hope, Kwame Nkrumah (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
The paper sought to design and evaluate a simple and affordable drip irrigation system for improving yield in backyard maize in Ghana. The design consisted of locally made system using easily available materials. The system was calibrated to obtain uniform flow. Hydraulic performance of the system was determined. A Randomize Complete Block Design with three depth treatments (T1=0cm, T2= 20cm and T3 = 40cm) and four replications was used. Plant parameters such as height, leaf length, leaf diameter and stem girth were measured weekly. The uniformity coefficient (UC) ranged from 98 to 99.8% signifying excellent water uniformity application. However, Flow and Coefficient of Variation (CV) values were below standard (ranged between 57.62 % to 60.60 % and 19.8 % to 23 % respectively) due to variation in pressure head. Maize growth under the developed drip lines gave good results in all the growth parameters and yield except the T3 but were statistically similar in all the treatments.